A qualitative exploration of pharmacist prescribing for patients with Chronic Kidney Disease in the United Kingdom. (26th March 2021) - Alraiisi, F; Stewart, D; Fahmy, M; Cunningham, S
Abstract: Introduction: Chronic Kidney Disease (CKD) has a high risk of mortality, frequent hospitalisation and reduced life expectancy. Clinical pharmacy services have potential to contribute significantly to the multidisciplinary team. In the UK Government policies prioritise development of pharmacist prescribing and the GPhC highlight changing health services that increasingly use pharmacist prescribers. Aim: To explore the development, implementation and evaluation of pharmacist prescribing for patients with Chronic Kidney Disease (CKD) in the UK. Method: This phase of a doctoral research programme used a phenomenological qualitative semi-structured interview approach. It involved 48 pharmacist prescriber members of the UK Renal Pharmacy Group (UKRPG) who had agreed to further research after an online survey. The development of the theory based semi-structured interview tool followed a rigorous iterative process using findings from a systematic review in the first phase [1] and results from a survey in the second phase.[2] The tool was designed using the Consolidated Framework for Implementation Research (CFIR) and reviewed independently for face and content validity by an expert panel. Think aloud testing and piloting completed the development process. A date / time for an audio-recorded telephone interview was arranged following receipt of signed consent. All interviews were transcribed verbatim naturalistically. NVivo® 11 was used for data management and analysis. Interview data were analysed thematically, guided by the CFIR, initially by two team members independently. The Francis method of checking for data saturation was used. Ethical approval was granted by RGU School of Pharmacy & Life Sciences Ethics committee. Results: Fourteen pharmacists of the 48 agreed to participate. Demographic details included: 11 female, 7 had >16 year experience in profession, all had secondary care as main practice setting and 8 had > 11years as a prescriber. The interviewees were generally very positive about their prescribing practice and they articulated that they were prescribing in a variety of settings. They used mainly independent prescribing in both inpatient and/or outpatient settings and prescribing in clinic settings for CKD associated anaemia / epoetin clinics. CFIR helped identify themes related to facilitators and barriers to advancing prescribing practice (Table 1). There was enthusiasm for the future development of prescribing practice including further establishment of clinics and taking responsibility for groups of patients. Interviewees indicated awareness of systems for evaluating their prescribing activity. Conclusion: This work provides valuable information relating to the current status of and needs for the development of pharmacist prescribing practice in the UK. It fills a gap shown from previous work [1] around availability of information on structures, process and monitoring of outcomes of this specific growing aspect of clinical pharmacy practice. Main strengths include consideration of aspects of trustworthiness throughout the research process aided by theoretical underpinning with CFIR and the focus on specialist pharmacist prescribers. Major limitations include low number of participants with consequent potential for recruitment and social desirability biases and lack of transferability of findings. Further 'deep dive' case study work will help explore the practice of leading edge advanced and consultant level practitioners to learn even more about practice development. References: 1. Al Raiisi F, Stewart D, Fernandez-Llimos F, Salgado TM, Fahmy Mohamed M, Cunningham S. 2019. Clinical pharmacy practice in the care of Chronic Kidney Disease patients: a systematic review. Int J Clin Pharm. 2019 41(3):630–666. doi: 10.1007/s11096-019-00816-4. 2. Al Raiisi F, Stewart D, Ashley C, Fahmy M, Alnaamani H, Cunningham S. A theoretically based cross-sectional survey on the behaviors and experiences of clinical pharmacists caring for patients with chronic kidney disease. Res Social Adm Pharm. 2020 May. In press, https://doi.org/10.1016/j.sapharm.2020.05.005